Characterization of sacha inchi (Plukenetia volubilis) and taro (Colocasia esculenta) flours with potential application in the preparation of both gluten-free and high protein foods. [version 4; peer review: 1 approved, 2 approved with reservations, 2 not approved] - Jesús Eduardo Bravo Gómez; Ruby Aracely Narváez Cadena; Angie Paola Salas Zambrano; Karen Sofia Muñoz Pabon; Diego Fernando Roa-Acosta (F1000Research)
Background Interest in alternative sources of tubers and legumes has increased due to the search for raw materials with bioactive antioxidant compounds. The objective of this study was to characterize taro (TF) and sacha inchi (Plukenetia volubilis) flours obtained by the wet (SIF-WM) and defatted (SIF-DM) methods, as alternatives for the formulation of functional foods. Methods Proximal tests were conducted to determine basic chemical composition, quantification of free polyphenols, antioxidant activity using the ABTS* radical method (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) with Trolox as a standard, and rheological analyses, including pasting curves, flow profiles, and viscoelastic properties. Microbiological characterization of the flours was also performed. Results The highest protein content was found in sacha inchi flour obtained by the defatted method (72.62%), while carbohydrates were the main component in taro flour (85.4%). In terms of antioxidant activity, taro flour showed higher values of 2.71 µmol ET/g and 7.47 mg EAG/g. Rheological analysis showed that adding taro flour increased the viscosity peak and reduced breakdown, improving gel stability. Staphylococcus aureus and Salmonella spp. were detected in taro flour. Conclusions Taro and sacha inchi flours have great potential for the development of functional products like protein snacks, with good expansion due to taro starch and are naturally gluten-free, making them suitable for people with celiac disease.